Work ethics and work values : a generational perspective - Sobayeni, Ntomzodwa Caroline (Welkom: Central University of Technology, Free State, 2015)
Although generational cohorts have been studied extensively in past years, not much information is available about generational cohorts and how they differ in terms of work values and work ethics in the South African context. The aim of this research study was to confirm the findings of research conducted in other countries, and to extend the current limited body of knowledge with regard to the work values and work ethics of different generational cohorts for a South African sample. A cross-sectional study was conducted with a sample of 301 employees from the South African labour force. Work values and work ethics of three generational cohorts were measured, namely the Baby Boomers, Generation X, and Generation Y. The data was analysed by means of a Mann-Whitney U test and Kruskal-Wallis tests, in order to determine the influence of the demographic variables on the dependent variables (i.e. workplace values and work ethics). Spearman rank-order correlations were performed to determine the relationships between the subcategories of the dependent variables. To establish the reliability of the measuring instruments, Cronbach’s alpha coefficients were determined. The main finding of this research was that statistically significant differences were found between the various generational cohorts in terms of work values and work ethics. Statistically significant differences were noted for the following work values: aesthetics, risk, social interaction, altruism, creativity, cultural identity, personal development, prestige, and variety. With regard to work ethics, statistically significant generational differences were indicated for hard work and delay of gratification. The findings of the study enable a more in-depth understanding of the work values and work ethics of different generational cohorts, which holds important implications for organisations. This research confirmed the importance of studying different generational cohorts in the context of the workplace.
Thesis
Keywords: generational cohorts; work values; work ethics; Generation X; Generation Y; the Baby Boomers